Problemy prawne dziedzieczenia praw autorskich - Charytonowa, Olena Ivanivna; Харитонова, Олена Іванівна; Kharitonova, Olena I. (My University, 2017)
W. Artikule analizue kwestie, które pojawiają się w związku z dziedziczenie praw autorskich. Tematem jest kwestii dziedziczenia osobistych praw niemajątkowych autora. Jest to związane zarówną z tą okolicznością, iż dziedziczenie praw majątkowych autora praktycznie nie różni się znacznie od dziedziczenia innych praw majątkowych, jak również z obecnością szeregu badań naukowych, w których odpowiednie kwestie zostały dość gruntownie zbadane. Specyfika dziedziczenia osobistych praw niemajątkowych autora spowodowana jest przez ich istotę, przynależność personalną, treść i ukierunkowanie. Zaznaczono, ze problem dziedziczenia osobistych praw niemajątkowych autora związany jest przede wszystkim z brakiem dokładnej regulacji odpowiednich stosunków w Kodeksie Cywilnym Ukrainy, a także z rozbieżnością pomiędzy przepisami rozdziału 84 KC Ukrainy oraz Ustawy Ukrainy „O prawie autorskim i prawach pokrewnych». W tej kwestii zrobiono analizę systemową przepisów prawa.

Стаття присвячена проблемам спадкування авторських прав, пов’язаним з наявністю двох видів таких прав – майнових і немайнових, щодо яких встановлено різний режим спадкування. Особисті немайнові права інтелектуальної власності, на відміну від майнових, не можуть бути об’єктом спадкування, однак у законодавстві містяться суперечливі та неоднозначні норми щодо цього положення. На такому підґрунті проводиться аналіз окремих немайнових прав автора з точки зору можливості або неможливості їх спадкування.

The objects of inheritance are the heir’s civil rights and duties which are inheritable. At the same time this does mean any rights and duties held by the heir as of the time of opening of inheritance but only those the existence of which are not terminated with the natural person’s death. Considering problem areas of inheriting author’s personal nonproperty rights are of great interest whereas inheritance of author’s property rights practically has no significant differences from inheritance of other property rights. The problem of inheriting author’s personal nonproperty rights is connected with the lack of clear regulation of corresponding relations in the Civil Code of Ukraine as well as gaps between the provisions of chapter 84 of the Civil Code of Ukraine and the Law of Ukraine «On Copyright and Related Rights». Personal nonproperty rights of intellectual property cannot be conveyed (transferred), with the exceptions established by the law. More specific and categorical order can be found in part II of article 14 of the Law of Ukraine «On Copyright and Related Rights» requiring that author’s personal nonproperty rights are not to be transferred to other persons. In addition to this in part I of article 29 of the same Law it is clearly specified that author’s personal nonproperty rights are not inherited. Therefore, the Law of Ukraine «On Copyright and Related Rights» directly prohibits the transition of personal nonproperty rights to the deceased author’s heirs by inheritance. Along with this, part II of article 29 of the mentioned Law contemplates that heirs have the right to protect authorship to creative products and resist to any changes of the work as well as any other interference to the work which could inflict harm to honor and image of the author. Thus, it is referred to a nonproperty right to inviolability of a creative product, the essence of which lies in the fact that in the process of publishing, public performance or other use of a piece of work it is prohibited to make any changes or disfigurations to both the work itself and its name without the permission of the author or his legal successors. It is also prohibited to add illustrations, introductions, concluding remarks, commentaries or any other explanations to the piece of work, supplement or reduce it without author’s permission. In this connection the question arises concerning the problem what is the basis for the emergence of such rights for heirs as the right to protect authorship to a piece of creative work, the right to demand protection of its integrity, resist any changes or disfigurations of the work etc. As it appears to be, the answer to this question is in the provisions of part IV of article 423 of the Civil Code of Ukraine where some exceptions referring transfer of personal nonproperty rights are denoted. It is possible to agree with the point of view expressed in literary sources that transfer to heirs of the right to inviolability of a piece of work is the mentioned above exception. Such opinion is also eligible to some extent in the provisions of part II of article 439 of the Civil Code of Ukraine which stipulate that in the case of author’s death the inviolability of a piece of work is secured by the person authorized by the author. With the absence of such power, the inviolability of a piece of work is protected by the author’s heirs as well as by other concerned parties Therefore, we can conclude that the right to inviolability of a piece of work arises with the moment of its creation but it is not terminated with the author’s death, particularly, it may be transferred to his heirs.
Charytonowa O. I. Problemy prawne dziedzieczenia praw autorskich / O. I. Charytonowa // Часопис цивілістики. – 2017. – Вип. 23. – С. 67-72.
Keywords: dziedziczenia; prawa własności; prawa własności; prawa autorskie; спадкування; немайнові права; майнові права; авторське право; inheritance; property rights; property rights; copyright